Development of 3D-Printed Bicompartmental Devices by Dual-Nozzle Fused Deposition Modeling (FDM) for Colon-Specific Drug Delivery - Fatemeh Shojaie; Carmen Ferrero; Isidoro Caraballo (MDPI AG, 2023)
Dual-nozzle fused deposition modeling (FDM) is a 3D printing technique that allows for the simultaneous printing of two polymeric filaments and the design of complex geometries. Hence, hybrid formulations and structurally different sections can be combined into the same dosage form to achieve customized drug release kinetics. The objective of this study was to develop a novel bicompartmental device by dual-nozzle FDM for colon-specific drug delivery. Hydroxypropylmethylcellulose acetate succinate (HPMCAS) and polyvinyl alcohol (PVA) were selected as matrix-forming polymers of the outer pH-dependent and the inner water-soluble compartments, respectively. 5-Aminosalicylic acid (5-ASA) was selected as the model drug. Drug-free HPMCAS and drug-loaded PVA filaments suitable for FDM were extruded, and their properties were assessed by thermal, X-ray diffraction, microscopy, and texture analysis techniques. 5-ASA (20% w/w) remained mostly crystalline in the PVA matrix. Filaments were successfully printed into bicompartmental devices combining an outer cylindrical compartment and an inner spiral-shaped compartment that communicates with the external media through an opening. Scanning electron microscopy and X-ray tomography analysis were performed to guarantee the quality of the 3D-printed devices. In vitro drug release tests demonstrated a pH-responsive biphasic release pattern: a slow and sustained release period (pH values of 1.2 and 6.8) controlled by drug diffusion followed by a faster drug release phase (pH 7.4) governed by polymer relaxation/erosion. Overall, this research demonstrates the feasibility of the dual-nozzle FDM technique to obtain an innovative 3D-printed bicompartmental device for targeting 5-ASA to the colon.